DEVELOPING INSTITUTIONAL HARMONY AND DEPARTMENTAL RESPECT THROUGH EAP: MATERIALS DEVELOPMENT - Ulgu, Serkan; Er, Mustafa (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿﻿﻿Harmony among the different departments of a university has always been critical from the perspective of teaching English as a second/foreign language (ESL/EFL) since it directly affects the English Language Teaching Program of a university. By ‘program’, we mean English at both the preparation class and during the faculty. TurAFA is a different and unique military academic institution in that the graduates of the academy receive two degrees: one commissioned officer, two a BA degree of currently five different departments following four-year education and training. English is of great importance for the prospective graduates of TurAFA for both their military and academic career. A certain proficiency of English will be indispensable aspect of the graduates who will be in need of English either for their tasks and missions both in homeland and abroad or for their academic studies during and after graduation. Therefore, a unique English Language Teaching Program has been developed in terms of schedule and content based on an intensive study of needs analysis and materials development since 2007. A hybrid experimental design (quantitative and qualitative) has been set up from the very beginning in order to observe and evaluate the effectiveness of the program in terms of developing harmony among the departments and developing respect among the learners and the academicians on the part of the curriculum developers, syllabus designers and materials developers. It has also been investigated how developing materials for EAP course increased the awareness of academicians in terms of TurAFA English Language Teaching Program.